2012
DOI: 10.1370/afm.1373
|View full text |Cite
|
Sign up to set email alerts
|

How Family Physicians Address Diagnosis and Management of Depression in Palliative Care Patients

Abstract: PURPOSE Depression is highly prevalent in palliative care patients. In clinical practice, there is concern about both insuffi cient and excessive diagnosis and treatment of depression. In the Netherlands, family physicians have a central role in delivering palliative care. We explored variation in family physicians' opinions regarding the recognition, diagnosis, and management of depression in palliative care patients. METHODSWe conducted a focus group study in a sample of family physicians with varied practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 33 publications
4
31
0
Order By: Relevance
“…15,16 Health professionals have reported difficulties with assessing and managing depression in the palliative care setting. [17][18][19][20] In particular, the distinction between depression and sadness or grief has been reported as challenging by family physicians, 20 palliative medicine physicians, 17 nurses, 18 and professional carers. 19 In a U.K. survey, palliative medicine physicians reported using an assortment of screening methods to assess for depression and endorsed different symptoms as useful for this purpose, 17 whereas general practitioners in the Netherlands emphasized clinical judgement of contextual factors in their assessment.…”
mentioning
confidence: 99%
“…15,16 Health professionals have reported difficulties with assessing and managing depression in the palliative care setting. [17][18][19][20] In particular, the distinction between depression and sadness or grief has been reported as challenging by family physicians, 20 palliative medicine physicians, 17 nurses, 18 and professional carers. 19 In a U.K. survey, palliative medicine physicians reported using an assortment of screening methods to assess for depression and endorsed different symptoms as useful for this purpose, 17 whereas general practitioners in the Netherlands emphasized clinical judgement of contextual factors in their assessment.…”
mentioning
confidence: 99%
“…In general, this is assumed to be small because criteria for diagnosis are discussed in monthly meetings, where the application of diagnostic criteria is monitored. However, GPs may have different views or different ways of assessing depressive disorder in the last phase of life 15 that has not been monitored specifically. Furthermore, in interpreting the findings of this study, it must be considered that depressive disorder throughout the 20 years of data that were included in this study may not have been a stable concept.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Indeed, a recent focus group study showed that while GPs are sometimes reluctant to classify sadness as depression in a palliative care context, they frequently attend to normal sadness in palliative care patients. 15 GPs can attend to emotional issues in a palliative care context without dichotomising the complex pattern of complaints into normal or disorder and with a explicit focus on the context of the depressive complaints that the patient experiences.…”
Section: Discuss This Articlementioning
confidence: 99%
See 2 more Smart Citations